Analisis Strategi Pemasaran Produk Cicil Emas di Bank Syariah Indonesia KCP Magelang Gatot Soebroto - Azizah, Anisatul; Fitriyani, Yeny; Purwanto, Purwanto (Forum Kerjasama Pendidikan Tinggi, 2023)
The research aims to learn more deeply about the marketing strategies carried out by the Indonesian Sharia bank KCP Magelang Gatot Soebroto in marketing Cicil Emas products to the public. The research method used in this research is field research with qualitative methods. The data sources used are primary data from interviews and secondary data from previous research documents. Data collection techniques use interviews, observation and documentation methods. The research results show that the marketing strategy using the 7P marketing mix, namely product, price, place, promotion, people, physical evidence and process for financing the Gold Installment investment, is good. It's just that there needs to be re-optimization of the strategies that have been implemented at Bank Syariah Indonesia KCP Magelang Gatot Soebroto, such as socialization and utilizing available social media such as webinars or interesting video content so that the marketing reach is more comprehensive and increases public understanding of Cicil Emas products.